Modeling and Docking of Cysteine Protease-A (CPA) of Leishmania donovani - Sindhuprava Rana, Jay Prakash Mahato, Maneesh Kumar, Surendra Sarsaiya (Journal of Applied Pharmaceutical Science, 2017)
Leishmaniasis is a tropical disease and causes severe public health issues. The disease caused by parasitic protozoan Leishmania species. Many people around the globe are affected in dramatic way, which would be fatal if untreated. Drugs have been made that become resistant to present strains. Cysteine proteases (CPs) are common protein degrading cysteine protease enzymes present in Leishmania donovani. In present scenario, to achieve effective enzyme inhibition mechanism, it should be taken into consideration to develop some effective and novel inhibitors to block the binding sites of that protein. Homology modeling of cysteine protease has been done and docked with suitable inhibitors by using various servers and computational tools. The model was designed, compared and validated by DOPE and Verify 3D scores by using DSv3.5. Licochalcone-a alone showed 37 LibDock conformations with 6 different poses were suitably docked at the site 1. The study would help to design the protein with new drugs in respect of resistant one for the treatment of harmful visceral leishmaniasis.
Keywords: Leishmaniasis, Cysteine proteases, LibDock, Computational, tropical disease.